Association between peripheral IFN-γ+ cytotoxic lymphocytes and response to PD-1/PD-L1-based therapy in hepatocellular carcinoma - Lu, Hui; Fang, Huijuan; Ruan, Mengqi; Duang, Zhi; Wang, Yan; Liu, Wenwen; Wang, Qin; Zhou, Qiang (Frontiers in Immunology, 2026)
BackgroundProgrammed cell death protein 1 (PD-1)/programmed death-ligand 1 (PD-L1)-based immune checkpoint therapy (ICT), either alone or in combination with tyrosine kinase inhibitors (TKIs) or bevacizumab, benefits a subset of patients with hepatocellular carcinoma (HCC), and reliable predictive biomarkers remain limited.MethodsBetween August 2024 and July 2025, 55 HCC patients treated with PD-1-based therapies were included. Objective response rate (ORR) was assessed according to the modified Response Evaluation Criteria in Solid Tumors (mRECIST). Peripheral cytotoxic lymphocyte subsets and effector functions were profiled by multiparameter flow cytometry. ResultsWe observed that the ICT plus TKI group exhibited a higher ORR than ICT monotherapy (54.5% vs. 29.4%; n = 22 vs. n = 17), whereas the ORR in the ICT plus bevacizumab group was comparable to ICT monotherapy (37.5% vs. 29.4%; n = 16 vs. n = 17). Compared with ICT monotherapy, patients receiving ICT plus TKI therapy had higher peripheral CD8⁺ cytotoxic T lymphocyte (CTL) proportions and elevated percentages of IFN-γ+ CTLs, natural killer (NK) cells, and natural killer T (NKT) cells (all P < 0.05). Across all treatment regimens, IFN-γ+ cytotoxic lymphocytes frequencies were associated with treatment response and showed good discrimination, whereas circulating serum IFN-γ levels were not informative.ConclusionThese findings support peripheral IFN-γ+ cytotoxic lymphocytes as a candidate noninvasive biomarker for stratifying HCC patients receiving PD-1/PD-L1-based therapy.